UPAYA MENCIPTAKAN MINAT MEMBACA DI KALANGAN ANAK MUDA KAMPUNG CIKALONG - Muhammad Muldani Azis; Adah Aliyah; Nandi Rustandi (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Reading is one of the methods to improve the quality of adequate human resources, the role of reading is very important for all circles. Reading is a characteristic of the decline and progress of this nation. Low interest in reading is the root cause of the difficulty of developing each individual. Therefore, it is very important to create an interest in reading in order to improve the quality of human resources and add value to each individual. This research aims to create interest in reading among young people and improve reading literacy in Cikalong Village, Jayabakti Village, Sukabumi District, West Java. This research method is descriptive qualitative with data collection techniques using the interview method, digging in-depth information through questions. Based on interviews, the role of young people is needed in the midst of society in the technological era. To bring young people into quality human resources, productive steps are needed. Precisely the young people of Cikalong Village really need facilities in reading which play a role in sharpening the thinking power of young people. But the young people of Cikalong village are still young people who are not productive and still lack critical thinking. Therefore, by creating reading facilities able to answer these problems, in order to become creative, productive, innovative and independent young people.